MASKULINITAS, KEKERASAN, DAN NEGARA DALAM THE RAID: REDEMPTION - Danial Hidayatullah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
Contestation of dominant masculinity in Indonesian Popular Culture influenced by the New Order can still be seen in its cinematic production. The legacy of The New Order echoes through themes of state’s violence and masculinity. The Raid: Redemption, as a huge international success, depicting vulgar violence done both by the state and the gangsters is very important to be analyzed. As the form of collective dreams, the contestation of masculinity and violence of the state and the gangster in the movie reflects the real social condition. Through historical perspective the state and the gangster are more like binary opposition; inseparable but opposing each other. The Gangsters became the state’s Frankenstein monster. On one side the state cannot allow the crime the gangsters do, but on the other the state keeps in creating the gangsters to the dirty jobs that state cannot do. Psychoanalytically speaking, their relationship resembles a father and a bad son. Those gangsters are “the son” and the state is “the father”. The effect of the state’s treatment to the gangsters can still be identified long after the down fall of the era that created it.